Ligand-functionalized degradable polyplexes formed by cationic poly(aspartic acid)-grafted chitosan–cyclodextrin conjugates. Issue 13 (11th March 2015) - Song, Hai-Qing; Li, Rui-Quan; Duan, Shun; Yu, Bingran; Zhao, Hong; Chen, Da-Fu; Xu, Fu-Jian
Abstract : Different types of ligand-functionalized degradable polyplexes were readily prepared for tumor cell-targeting gene delivery based on the cationic poly(aspartic acid)-grafted chitosan–cyclodextrin conjugates. Abstract : Polypeptide-based degradable polyplexes attracted considerable attention in drug delivery systems. Polysaccharides including cyclodextrin (CD), dextran, and chitosan (CS) were readily grafted with cationic poly(aspartic acid)s (PAsps). To further enhance the transfection performances of PAsp-based polyplexes, herein, different types of ligand (folic acid, FA)-functionalized degradable polyplexes were proposed based on the PAsp-grafted chitosan–cyclodextrin conjugate (CCPE), where multiple β-CDs were tied on a CS chain. The FA-functionalized CCPE ( i.e., CCPE-FA) was obtained via a host–guest interaction between the CD units of CCPE and the adamantane (Ad) species of Ad-modified FA (Ad-FA). The resulting CCPE/pDNA, CCPE-FA/pDNA, and ternary CCPE-FA/CCPE/pDNA (prepared by layer-by-layer assembly) polyplexes were investigated in detail using different cell lines. The CCPE-based polyplexes displayed much higher transfection efficiencies than the CS-based polyplexes reported earlier by us. The ternary polyplexes of CCPE-FA/CCPE/pDNA produced excellent gene transfection abilities in the folate receptor (FR)-positive tumor cells. This work would provide a promising means to produce highly efficient polyplexes for future gene therapy applications.